PERBANDINGAN PENERAPAN MODEL PEMBELAJARAN PEER MEDIATED INSTRUCTION AND INTERVENTION DAN MODEL PEMBELAJARAN THINK PAIR-SHARE TERHADAP HASIL BELAJAR BIOLOGI - Adha Kurnianti; Ilyas Ismail; Sitti Mania (Jurnal Biotek, 2016)
This research is motivated by the problems derived from the observation that low motivation and activeness and student learning outcomes in learning biology, evident from the study of biology class VII SMP Negeri 2 Bajeng West, in general, students received grades that are still under the KKM. In this study, researchers used peer learning model Mediated Instruction and Intervention (PMII) type Peer Mediated Instruction And Intervention (CWPT) and learning model Think Pair-Share (TPS) to foster motivation and activeness of student learning.This study aims to (1) To determine the result of studying biology class VII SMP Negeri 2 Bajeng Gowa on the subject of diversity of living creatures that learned learning model Peer Mediated intruction and Invention (PMII) type Class Wide Peer Tutoring (CWPT) (2) to find out the results of studying biology class VII SMP Negeri 2 Bajeng Gowa on the subject of diversity of living creatures that learned and learning model Think Pair-Share (TPS) (3) to determine differences in learning outcomes biology class VII SMP Negeri 2 Bajeng Gowa on the subject of diversity of living creatures that learned to Peer Mediated learning model intruction and Intervention (PMII) type Class Wide Peer Tutoring (CWPT) and learning model Think Pair-Share (TPS).This study is a quasi-experimental research (quasi) using a pretest-posttest design nonequivalent control group design. The population of this study were all students of class VII SMP Negeri 2 Bajeng Gowa district in 2015/2016 academic year consisting of five study groups totaling 151 students, with a sample of 25 people in the class VIIB and 25 people in the class VIIA.The results showed that the obtained tcount 1,680 <ttable 2,000 and significance (0.000 <0.05), suggesting that H0 and H1 accepted, so it can be concluded that there is positive and significant difference in the application of learning models Peer Mediated Instruction and Intervention (PMII) type class Wide Peer Tutoring (CWPT) to class VIIB using learning model Think Pair-Share (TPS) for class VIIA.